2013
DOI: 10.1111/jch.12080
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Risk of Incident Hypertension in a Korean Middle‐Aged Population: Korean Genome and Epidemiology Study

Abstract: The objectives of this study were to construct a risk score for predicting incident hypertension by using the Korean Genome and Epidemiology Study (KoGES) data and to compare the performance between KoGES and the Framingham model. A total of 4747 participants were analyzed. The entire cohort was randomly assigned to derivation and validation sets at a ratio of 6:4. A hypertension risk score was developed based on the derivation cohort, using the same risk factors that were used for developing the Framingham hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 23 publications
(49 reference statements)
3
51
0
Order By: Relevance
“…22 Similarly, our previous study in a Korean population demonstrated that the Framingham risk score underestimated risk for HT even though the individuals in both studies had similar risk factors at baseline. 13 Although the discrimination was similar to that in the Framingham Offspring Study, concordance between observed and predicted risk was poor even after recalibration of the Framingham model, suggesting that risk models may not be accurate in different ethnic populations even after adjusting the model. Another study in a Chinese cohort showed that the Framingham model had good calibration but lower discrimination than risk models developed from the original cohort.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…22 Similarly, our previous study in a Korean population demonstrated that the Framingham risk score underestimated risk for HT even though the individuals in both studies had similar risk factors at baseline. 13 Although the discrimination was similar to that in the Framingham Offspring Study, concordance between observed and predicted risk was poor even after recalibration of the Framingham model, suggesting that risk models may not be accurate in different ethnic populations even after adjusting the model. Another study in a Chinese cohort showed that the Framingham model had good calibration but lower discrimination than risk models developed from the original cohort.…”
Section: Resultsmentioning
confidence: 97%
“…13 Most risk scores used to predict HT have not been validated externally in a different data source. According to a recent review article, only the Framingham and Hopkins scores have been evaluated in populations or ethnic groups that are different from those used for initial development of the model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several risk prediction models for incident hypertension have been recently developed in Western, [13][14][15][16][17] Middle Eastern 18 and Asian 19,20 countries. Most of these models 13,14,[16][17][18][19][20] consist of simple clinical parameters and self-reported data, including information regarding lifestyle factors.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these models 13,14,[16][17][18][19][20] consist of simple clinical parameters and self-reported data, including information regarding lifestyle factors. The simplicity and user-friendliness of these models allow for their easy application in daily clinical practice as tools designed to prevent hypertension.…”
Section: Introductionmentioning
confidence: 99%